TINJAUAN KRITIS TERHADAP UNDANG-UNDANG NOMOR 8 TAHUN 2019 TENTANG PENYELENGGARAAN IBADAH HAJI DAN UMRAH OLEH KEMENAG KABUPATEN SORONG - Latif, Udin; Hidayat, M. Akbar (Muadalah : Jurnal Hukum, 2024)
The implementation of the pilgrimage has an important role for all Muslims around the world. Hajj completes the other 4 worships in the pillars of Islam. The implementation of the pilgrimage requires knowledge, guidance and direction from people who are experienced in the field of Hajj. The implementation of the pilgrimage carried out by the Ministry of Religion of the Republic of Indonesia can be an additional reference for prospective Hajj participants. The results of the study show that the implementation of the pilgrimage carried out by the Ministry of Religion of Sorong Regency is in accordance with the mandate of Law No. 8 of 2019 plus regulations from the Minister of Religion and also based on Islamic Shari'a guided by the Qur'an and the Sunnah of the Prophet Muhammad SAW. Increase knowledge to prospective pilgrims about the implementation of the pilgrimage and other knowledge and insights. Together with the Ministry of Religion, Sorong Regency, the success of the Hajj pilgrimage in Sorong Regency.